Information System and Population Data Search Using the Boyer-Moore Algorithm in Nagari Kotobaru Simalanggang - Sukma, Fanni; Hadi, Ronal; Chairani, Fitri; Sariani; Wardhani, Aditya (International Journal of Advanced Science Computing and Engineering, 2023)
The growth of information technology throughout the world is now faster and stronger than before, one of which is Information Systems. The development of the Nagari information system in Kotobaru Simalanggang aims to increase the efficiency of Nagari administrative staff in searching for population data while making it easier for the public to manage administrative documents such as correspondence. This system enables users to process documents such as letters through a special website. To improve the accuracy of data searches, the Boyer-Moore algorithm was used, with Population Identification Numbers (NIK) and resident names as search criteria. The Laravel framework with Model-View-Controller (MVC) architecture is used to create this website. The waterfall technique is used in the research process. This strategy was chosen because each stage must wait for the preceding stage to be completed before proceeding. In data search, the implementation of the Boyer-Moore method yields a 100% accuracy rate. This guarantees that the public receives the most relevant information.